Розумні датчики мобільних роботів - Гудиря, Я. І. (ХНУРЕ, 2025)
The purpose of the work is the use of sensors in robotics. The term smart sensor can mean different things to different people. One definition relates intelligent sensors to applications belonging to the Internet of Things (IoT), that is, to collect information and provide data for organizing control and management, as well as optimizing industrial processes and applications.
Keywords: розумний датчик; мобільний робот